Design of Automatic Deforestation Protection System - Shibani Sahu, Priyadarshini; Pattanai, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
Illicit logging has been recognized as a significant issue in all over the world, which might be limited through successful observing of forest territories. This paper proposes and depicts the underlying strides to construct another three-level design for Forest Monitoring dependent on IoT and tree cutting noise identification by utilizing various sensors. The manual checking of the timberland to anticipate unapproved exercises is a very difficult job. The four significant tasks that are basic in analyzing the forest are developed in this work, in particular, tree cutting location, fire recognition, human discovery and tainted water identification utilizing vibration sensor, fire sensor, Passive Infrared Sensor (PIR) and PH sensor separately. A microcontroller is utilized along with GSM to convey to the focal server from a remote place. The detected information from sensors is gathered and sent to the approved individual by means of GSM. IoT has generally utilized innovation in forest analyzing the application. Moreover, this paper utilizes a Wi-Fi switch module through which forest administrators and employees can communicate with one another if the network is crippled.